How do hotel employees' environmental attitudes and intentions to implement green practices relate to their ecological behavior?. (June 2019) - Okumus, Fevzi; Köseoglu, Mehmet Ali; Chan, Eric; Hon, Alice; Avci, Umut
Abstract: This study investigates the interaction effect of hotel employees' environmental attitudes and intentions to implement green practices to predict their ecological behavior. Based on our literature review, a model was proposed, and data were collected via survey from 497 hotel employees in Turkey. The study's findings reveal significant relationships between the employee-related factors and their ecological behaviors. More specific, the study's results found that employees' intention to implement green practices arising from work environment has a moderation effect on the relationships between three employee-related factors (environmental awareness, environmental concern, and environmental knowledge) and ecological behaviors. This is important for understanding how hotels can influence their employees' ecological behavior. This study provides specific theoretical and practical implications.